2019
DOI: 10.1021/jacs.8b11129
|View full text |Cite|
|
Sign up to set email alerts
|

Design Principle of Fe–N–C Electrocatalysts: How to Optimize Multimodal Porous Structures?

Abstract: The effect of porous structures on the electrocatalytic activity of N-doped carbon is studied by using electrochemical analysis techniques and the result is applied to synthesize highly active and stable Fe–N–C catalyst for oxygen reduction reaction (ORR). We developed synthetic procedures to prepare three types of N-doped carbon model catalysts that are designed for systematic comparison of the porous structures. The difference in their catalytic activity is investigated in relation to the surface area and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
274
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 438 publications
(294 citation statements)
references
References 50 publications
10
274
2
Order By: Relevance
“…Fe/OES exhibited a more positive onset potential (E O , 1.0 V vs. RHE) and half-wave potential (E 1/2 , 0.85 V vs. RHE) than Fe/BCS and other control samples, indicating the advantages of such an overhang-eave structure with the capability of boosting the mass transport of reactants. [31] The catalytic activity of Fe/OES was comparable to that of Pt/C (E 1/2 , 0.85 V vs. RHE) ( Figure S44) and outperformed those of most of the low-cost electrocatalysts reported to date (Tables S6,S7). Rotating-ring-diskelectrode (RRDE) measurements revealed that the electron transfer number (n) of Fe/OES was about 3.8-4.0 with a low peroxide yield of 1.1-13 % (Figure 3 e).…”
Section: Zuschriftenmentioning
confidence: 79%
“…Fe/OES exhibited a more positive onset potential (E O , 1.0 V vs. RHE) and half-wave potential (E 1/2 , 0.85 V vs. RHE) than Fe/BCS and other control samples, indicating the advantages of such an overhang-eave structure with the capability of boosting the mass transport of reactants. [31] The catalytic activity of Fe/OES was comparable to that of Pt/C (E 1/2 , 0.85 V vs. RHE) ( Figure S44) and outperformed those of most of the low-cost electrocatalysts reported to date (Tables S6,S7). Rotating-ring-diskelectrode (RRDE) measurements revealed that the electron transfer number (n) of Fe/OES was about 3.8-4.0 with a low peroxide yield of 1.1-13 % (Figure 3 e).…”
Section: Zuschriftenmentioning
confidence: 79%
“…To systematically investigate the effect of porous structures on the ORR, Lee et al synthesized three models of N‐doped carbon catalysts ( Figure 7 a), namely, standard (where macro‐, meso‐, and micropores coexisted), meso‐free (where only macro and micropores coexisted), and macro‐free (where only meso‐ and micropores coexisted). [ 105 ] These three model catalysts presented comparable BET surface areas but different pore size distributions (Figure 7b). [ 105 ] To quantitatively analyze the function of pores of different sizes, the electric double‐layer capacitance ( C dl ) of these three model catalysts were measured using two different methods: electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV).…”
Section: Molecular Design Of Sacs With Enhanced Orr Activitymentioning
confidence: 99%
“…[ 105 ] These three model catalysts presented comparable BET surface areas but different pore size distributions (Figure 7b). [ 105 ] To quantitatively analyze the function of pores of different sizes, the electric double‐layer capacitance ( C dl ) of these three model catalysts were measured using two different methods: electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV). The C dl values obtained using EIS response in the low frequency region ( C dl_ EIS) represented the total surface area that could be wetted by the electrolyte (electrochemically wettable surface area) under static conditions.…”
Section: Molecular Design Of Sacs With Enhanced Orr Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Porous carbon materials have received wide interest because of their attractive physicochemical properties, easy compatibility with other elements, and low cost and toxicity, as well as wide applications in energy storage and conversion, adsorption and catalysis [1][2][3][4][5][6][7]. A well-controlled pore structure is significantly important for these materials in various applications.…”
Section: Introductionmentioning
confidence: 99%